P2 Hybrid AMT Shift Clutch Engagement Control Strategy based on Model Prediction - Changqing Du; Huan Zhang; Xiliang Cao; Huawu Wang (Jixie chuandong)
The engagement process control quality of the clutch after AMT shift has a great influence on the impact of the system. For the engagement process of the P2 single-shaft parallel hybrid vehicle clutch， the two control targets of the clutch is engaged as soon as possible during the clutch engagement phase and the impact is as small as possible， the dynamics process of the clutch engagement phase in different driving modes is analyzed， a clutch engagement control strategy based on model predictive control is designed， an Amesim-Simulink joint simulation model is built to simulate and analyze the control strategy. The effect of predictive control is compared with the fuzzy PID control. The results show that the model predictive control method will slightly increase the clutch engagement time within an acceptable range， and the slip wear and impact will be reduced to varying degrees， of which the reduction in impact is particularly obviously， the degree of impact is reduced by 43% when the engine is driven alone， and by 35% when the drive is hybrid.